Upaya Pemerintah Afrika Selatan dalam Menghadapi Krisis Air Bersih di Cape Town 2015-2019 - Megantari, Ni Luh Putu Laksmi; Kawitri Resen, Putu Titah; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 1 (2022): Jurnal DIKSHI, 2022)
Cape Town which previously received the Adaptation Implementation award, since 2015 began to experience a drought which was then exacerbated by El Nino and climate change. Drought is getting worse that made South African government declare a water shortage in Cape Town. Water Shortage in Cape Town is further exacerbated by low rainfall which causes low dam levels so the city does not have supply of water that are used for daily needs of Cape Town. The government began to limit the level of water use in general in order to avoid more severe crisis. This thesis discusses the efforts of South African government in dealing with the water shortage that occurred in one of major cities of South Africa. This thesis also discusses how  South African Government has made domestic efforts that directly involve the community and external efforts by adapting international ways of dealing water shortage through cooperation. Key words : Water Shortage, Cape Town, South African Government, Climate Changes.